1998
DOI: 10.1103/physrevb.58.15160
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry of binding in doped antiferromagnets

Abstract: Using variational wave functions the construction of which is based on the ''string'' or ''spin bag'' picture, we calculate the energies of two-hole states classified according to the momentum and the different irreducible representations of the C 4v point group. We study different ratios J/t, interesting from the experimental viewpoint, and compare our results to exact diagonalization. The energetically most favorable pair symmetries are d x 2 Ϫy 2 and p like. The mechanism of hole binding is the caterpillar-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 29 publications
(46 reference statements)
6
51
0
Order By: Relevance
“…Note that this trend is consistent with the prediction from the spin polaron picture. 9,10,18 While at JϾ0.3t the p (,) and p (,0) states are clearly excited states, the energy levels look quite complicated in the range 0.2tрJр0.3t. Note that the d, p (,) and p (,0) states are almost degenerate at Jϭ0.3t, although the d state is still the ground state.…”
Section: Low-lying States With Different Symmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that this trend is consistent with the prediction from the spin polaron picture. 9,10,18 While at JϾ0.3t the p (,) and p (,0) states are clearly excited states, the energy levels look quite complicated in the range 0.2tрJр0.3t. Note that the d, p (,) and p (,0) states are almost degenerate at Jϭ0.3t, although the d state is still the ground state.…”
Section: Low-lying States With Different Symmetriesmentioning
confidence: 99%
“…Later it was shown that such pairing of holes at ͱ2 arises naturally if the wave function has d x 2 Ϫy 2 symmetry. 8,9 But in order to firmly establish the role of d-wave hole pairing in the theory of superconductivity, one has to understand how strong and robust the pairing is. In fact a numerical study 7 has shown that the binding energy of the d channel is negative but small and that the holes may not be tightly bound in real space.…”
Section: Introductionmentioning
confidence: 99%
“…10͑c͒. variational study of the t-J model, a similar effect has been observed in the context of the caterpillarlike movement of holes. 25 A rigorous account for the retardation yields modified equations for the bound-state energies, leaving the qualitative picture drawn in the static limit essentially unchanged:…”
Section: ͑43͒mentioning
confidence: 99%
“…Qualitatively similar questions have been addressed in a recent variational study of the hole pairing in the t-J model. 25 Our numerical ED results for the t-J z model are obtained…”
Section: Introductionmentioning
confidence: 99%
“…Despite the intensive work on this problem in the last 20 years, investigation of binding even within the single band models, like the t-J model, continued to represent a challenging task [2]. After extensive analytical as well as numerical efforts devoted to the two-hole problem in the t-J model [2][3][4][5][6][7][8], a general consensus has been established that the bound pair with a d-wave symmetry represents the ground state in a parameter range J/t 0.4. Nevertheless, in the regime J/t 1 the symmetry of the ground state crosses to p-wave, raising doubts of many authors about the relevance of the t-J model for high-T c superconductivity.…”
Section: Introductionmentioning
confidence: 99%